2017
DOI: 10.1177/2050640616663571
|View full text |Cite
|
Sign up to set email alerts
|

Splenic volume differentiates complicated and non‐complicated celiac disease

Abstract: Background: Studies in small groups of patients indicated that splenic volume (SV) may be decreased in patients with celiac disease (CD), refractory CD (RCD) type II and enteropathy-associated T-cell lymphoma (EATL). Objective: The objective of this article is to evaluate SV in a large cohort of uncomplicated CD, RCD II and EATL patients and healthy controls. Methods: The retrospective cohort consisted of 77 uncomplicated CD (of whom 39 in remission), 29 RCD II, 24 EATL and 12 patients with both RCD II and EAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Measuring spleen size is of interest in case of suspected/confirmed CD, as some small-sampled studies have linked splenic hypotrophy with CD and other have shown an association of small spleen volume with refractory CD [58,59,60].…”
Section: Hyposplenism and Susceptibility To Infectionsmentioning
confidence: 99%
“…Measuring spleen size is of interest in case of suspected/confirmed CD, as some small-sampled studies have linked splenic hypotrophy with CD and other have shown an association of small spleen volume with refractory CD [58,59,60].…”
Section: Hyposplenism and Susceptibility To Infectionsmentioning
confidence: 99%
“…Imaging studies may also aid disclosing abdominal masses and mesenteric lymphadenopathies (27, 38), heralding RCD-II and EATL-related complications (Table 1). Splenic atrophy is a further finding, especially in cases of RCD-II and EATL (39). Endoscopic studies should be integrated with biopsy sampling and histological re-evaluation.…”
Section: Diagnostic Workup Of Rcdmentioning
confidence: 99%
“…Laboratory tests are non-specific with anemia, high LDH and B2M levels and low serum albumin due to starvation (30,95). Imaging studies often reveal enteric strictures, perforations or mass lesions, as well as mesenteric adenopathies and/or splenomegaly (27,39). Although these findings are highly suggestive of EATL in the setting of CD, a definite diagnosis is only posed by histological evaluation of endoscopic biopsies or resection specimens.…”
Section: Clinical-prognostic Features Of Eatlmentioning
confidence: 99%
“…Hyposplenism is more common with concomitant autoimmune disease, old age at coeliac diagnosis, refractory coeliac disease or a history of major infections 127 . Reduced spleen volume on imaging is a marker for refractory coeliac disease 131 . As coeliac patients who have not had pneumococcal vaccination are at increased risk of community‐acquired pneumonia, 132 vaccination against pneumococcus is recommended and vaccination against the other main encapsulated bacteria Neisseria meningitidis and Haemophilus influenzae type B should be considered.…”
Section: Monitoring For Complicationsmentioning
confidence: 99%